Pengaruh Celebrity Endorser Dan Iklan Pada Media Sosial Instagram Terhadap Minat Beli Produk Perawatan Wajah (Studi Kasus Pada Konsumen Ms Glow) - Fiska Triwinda Witjaksari; Muhammad Ridwan Basalamah; Rahmawati Rahmawati (UNIVERSITAS ISLAM MALANG, 2022)
AbstractDigital advertising is currently a trend in society, one of which is advertising through social media such as Instagram. The purpose of this study was to determine the effect of Celebrity Endorsers and advertisements on buying interest in MS Glow treatment products in Malang City. This type of research is a quantitative study with a population of Malang City residents who buy skin care products who are active followers of Ms Glow's Instagram account (Have interacted with Ms Glow's account such as; Like, Comment, Share, Save, and Repost) and purposive sampling and obtained a sample of 100 respondents. The data were then analyzed by multiple linear regression with the help of SPSS 25 software. The results showed that Celebrity Endorser partially had no significant effect on buying interest in MS Glow treatment products. While advertising partially has a significant effect on the product of interest in buying MS Glow treatment. Celebrity Endorser and Advertisement variables simultaneously have a significant effect on buying interest in MS Glow treatment products., Keywords: Celebrity Endorser, Advertising, MS Glow